The optimum currency area theory and the EMU: An assessment in the context of the eurozone crisis - Jennifer Jager; Kurt A. Hafner (Intereconomics, 2013)
The eurozone crisis has revealed certain shortcomings of the EMU, such as its vulnerability to asymmetric shocks and its inability to act as predicted by the theory of optimum currency areas. Although the share of intra-EU trade has increased since the introduction of the euro, dissimilarities in economic structure combined with high degrees of industrial specialisation have increased the EMU's vulnerability to asymmetric shocks. Moreover, the lack of labour mobility or a transfer payment system limits the EMU's crisis adjustment capabilities. However, most of the implemented and proposed stabilisation measures seek to remedy this vulnerability by promoting economic integration, further fiscal discipline and debt redemption.
Keywords: 330; Eurozone; Makroökonomischer Einfluss; Optimaler Währungsraum; EU-Staaten